Heavy Metals and Pathways of Incorporation in the Soil, Sediments and Water Matrices of River Nzoia, Kenya - Tarus, S. J.; Kituyi, J. L.; Segor, F. K. (African Journal of Education,Science and Technology (AJEST), 2025)
For prudence in the management of lotic ecosystems, vital information on the degree of pollutant load is required. Several human activities are practiced within the River Nzoia catchment area, most of which result in heavy metals and/or their compounds most of which end up in different matrices of the river’s bio-system. Since metals cannot biodegrade, most of them will therefore exist in forms, thus affecting the biosphere of the river. This study was conducted to monitor spatial and temporal variations in the concentrations of heavy metals in water, soil and sediments of River Nzoia, in Western Kenya. The heavy metals analysed by atomic absorption spectrophotometer (AAS) were; zinc (Zn), lead (Pb), copper (Cu), chromium (Cr) and cadmium (Cd) from a total of eight stratified sampling stations located along the River Nzoia from Cherangani to Mumias. Sampling was done twice capturing the variability during the dry and rainy seasons in February 2007 and June 2007. Heavy metal levels were Zn [1.7789 ± 0.2982 mg/L], Pb [0.9409 ± 0.0076 mg/L], Cu [0.7041 ± 0.1026 mg/L], Cr [0.917 ± 0.00827 mg/L] and Cd [0.1748±0.00414 mg/L] exceeded the WHO limits (0.05 mg/L for Zn, Pb and Cu, 0.01 mg/L for Cr and Cd), in all the sites sampled. This showed that Nzoia River’s water is dangerously contaminated by these heavy metals. The catchment area was affected by temporal variations with higher values of heavy metals recorded during the rainy season.